Analysis of Liver Transplantation Outcome in Patients With MELD Score ≥30 - Ferraz-Neto, B.H.; Zurstrassen, M.P.V.C.; Hidalgo, R.; Meira-Filho, S.P.; Rezende, M.B.; Paes, A.T.; Afonso, R.C. (Transplantation proceedings, 2008)
Since July 2006, the liver graft allocation has been changed from the waiting time to the Model for End-stage Liver Disease (MELD), prioritizing the sickest patients, who have a higher risk of dying on the waiting list, and sometimes in such poor clinical condition that it compromises transplantation outcomes. The aim of this study was to analyze the impact of a MELD score ≥ 30 on 30-day survival after liver transplantation (OLT). We prospectively collected the data on 178 liver transplants on 163 patients performed from March 2003 to August 2007. The subjects were divided in two groups according to their MELD scores: group 1, MELD ≥ 30 ( n = 15) and group 2, MELD < 30 ( n = 96). The groups were compared with regard to hospital and intensive care unit (ICU) length of stay, intraoperative blood products transfusion, early survival (30 days), and need for retransplantation. We excluded, patients with prioritization criteria, those receiving extra points for any special situation, and six other patients without significant data for MELD calculation (of whom only one has died after transplantation). Patients under a “special situation” were those with hepatocelular carcinoma, hepatopulmonary syndrome, and metabolic diseases, who initially received a MELD/PELD score 20, and 24, and 29. The mean MELD score at group I was 34 (range, 30 to 42), and for group II it was 16 (range, 6 to 29). Group I displayed a mean hospital length of stay of 24 days (4 to 155), with 12.60 days (ranges, 1 to 103) in the ICU versus 15.55 (range, 1 to 48) and 5.13 (range, 1 to 45) days, respectively, for group II. The need for blood component transfusions were greater in group I; 25.28% of patients in group II did not receive any transfusion during the entire inpatient period. There were nine retransplants in group II, and none in group I. The 30-day survivals were 93.3% for group I and 84.37% for group II. Besides the increased complexity of these sickest patients, there was no negative impact on early survival rates.